An Iterative PSD-Based Procedure for the Gaussian Stochastic Earthquake Model with Combined Intensity and Frequency Nonstationarities: Its Application into Precast Concrete Structures - Xu-Yang Cao (Mathematics, 2023)
Earthquakes cause severe damage to human beings and financial development, and they are commonly associated with a lot of uncertainties and stochastic factors regarding their frequency, intensity and duration. Thus, how to accurately select an earthquake record and determine an earthquake’s influence on structures are important questions that deserve further investigation. In this paper, the author developed an iterative power spectral density (PSD)-based procedure for the Gaussian stochastic earthquake model with combined intensity and frequency nonstationarities. In addition, they applied this procedure to five precast concrete structures for dynamic analysis and verification. The research proved the effectiveness of the iterative procedure for matching the target response spectra and for generating the required seismic records. The application examples verified the accuracy of the seismic design for the precast concrete structures and indicated the reliable dynamic demands of the precast concrete structures under the stochastic excitation of nonstationary earthquakes. In general, the research provided a meaningful reference for further stochastic earthquake selections, and it could play an effective role in further assessments of precast structures.